Manajemen kinerja pelaku usaha pemasaran ikan di Tempat Pelelangan Ikan (TPI) Sodohoa Kota Kendari - Sari, Suci Indah; Lawelle, Sjamsu Alam; Mansyur, Akhmad; Risfandi; Budiyanto (Jurnal Sosial Ekonomi Perikanan, 2024)
This study aimed to determine the performance management of sales people of fish marketing business. This research was conducted at the Sodohoa Fish Auction Place, Kendari City in September 2022. The location for the research was determined by purposively. Data were obtained through interviews with respondents using a questionnaire method. The sample was determined by using a simply random sampling technique with a total amount of respondent was 60 respondents. The method used in this research is a quantitative descriptive method. The results showed that there were two groups of fish marketing business actors in fish auction in Sodohoa, namely salesmen and saleswomen. In general, saleswomen performance management in fish marketing was more better than salesmen performance. Partially, saleswomen were more better in planning and organizing aspects than salesmen, in a while, the salesmen were more better in actuating and controlling aspects